HUKUM KETERLIBATAN PEREMPUAN DALAM RANAH PUBLIK: Kajian Tafsir Tekstual dan Kontekstual - Musolli Musolli (JURNAL HAKAM, 2020)
The involvement of women in the public sphere should be accompanied by two theories, textual and contextual. These two theories appear to support a big agreement that the Koran is present in addition to being a solution but also providing innovation. The innovation offered is the concept that the Koran is suitable for every situation.Keywords: women, Koran, textual and contextual.